Transmission and Effect of Multiple Clusters of Seasonal Influenza in a Swiss Geriatric Hospital. Issue 4 (April 2015) - Pagani, Leonardo; Thomas, Yves; Huttner, Benedikt; Sauvan, Valérie; Notaridis, Grigorios; Kaiser, Laurent; Iten, Anne; Pittet, Didier; Harbarth, Stephan
Abstract : Objectives: To investigate a nosocomial outbreak of influenza. Design: Prospective outbreak investigation with active case finding and molecular typing. Setting: A large academic geriatric hospital in Switzerland. Participants: Elderly hospitalized adults. Measurements: Based on syndromic surveillance, a nosocomial influenza outbreak was suspected in February 2012. All suspected cases were screened for respiratory viruses using real‐time reverse transcription polymerase chain reaction of nasopharyngeal swabs. Infection control procedures (droplet precautions with single room isolation whenever possible) were implemented for all suspected or confirmed cases. Specimens positive for influenza viruses were processed and sequenced whenever possible to track transmission dynamics. Results: Respiratory samples from 155 suspected cases were analyzed during the outbreak period, of which 69 (44%) were positive for influenza virus, 26 (17%) were positive for other respiratory viruses, and 60 (39%) were negative. Three other cases fulfilled clinical criteria for influenza infection but were not sampled, and one individual was admitted with an already positive test, resulting in a total of 73 influenza cases, of which 62 (85%) were classified as nosocomial. Five distinct clusters of nosocomial transmission were identified using viral sequencing, with epidemiologically unexpected in‐hospital transmission dynamics. Seven of 23 patients who experienced influenza complications died. Sixteen healthcare workers experienced an influenza‐like illness (overall vaccination rate, 36%). Conclusion: Nosocomial influenza transmission caused more secondary cases than repeated community importation during this polyclonal outbreak. Molecular tools revealed complex transmission dynamics. Low healthcare worker vaccination rates and gaps in recommended infection control procedures are likely to have contributed to nosocomial spread of influenza, which remains a potentially life‐threatening disease in elderly adults.